Transvaginal Ultrasound Vibro-elastography for Measuring Uterine Viscoelasticity: A Phantom Study - Zhang, Xiaoming; Zhou, Boran; VanBuren, Wendaline M.; Burnett, Tatnai L.; Knudsen, John M. (Ultrasound in medicine & biology, 2019)
The purpose of this research was to determine the feasibility of a transvaginal ultrasound vibro-elastography (TUVE) technique for generating and measuring shear wave propagation in the uterus. In TUVE, a 0.1-s harmonic vibration at a low frequency is generated on the abdomen of a subject via a handheld vibrator. A transvaginal ultrasound probe is used to measure the resulting shear wave propagation in the uterus. TUVE was evaluated on a female ultrasound phantom. The shear wave speeds in the region of interest of the uterus of the female ultrasound phantom were measured in the frequency range of 100–300 Hz. The viscoelasticity was analyzed based on the wave speed dispersion with frequency. The measurement of shear wave speed suggests that the uterus of this female ultrasound phantom is much stiffer than the human uterus. This research illustrates the feasibility of TUVE for generating and measuring shear wave propagation in the uterus of a female ultrasound phantom. We will further evaluate TUVE in patients, both normal controls and those with uterine diseases such as adenomyosis.